Controllability and observability analysis of the gain scheduling based linearization for UAV quadrotor - Ataka, Ahmad; Tnunay, Hilton; Inovan, Reka; Abdurrohman, Muhammad; Preastianto, Hanry; Cahyadi, Adha Imam; Yamamoto, Yoshio (2013 International Conference on Robotics, Biomimetics, Intelligent Computational Systems, 2013)
This paper presents the gain scheduling based linearization of simplified quadrotor non-linear model as well as the test for the system controllability and observability for various equilibrium point. The simplified non-linear model of quadrotor is linearized at some equilibrium points to get the linear state equation. Then, the controllability and observability test is done to the linearized model for various equilibrium points. The system behavior is then tested by using the state feedback controller to confirm the result.